Сase of prenatal diagnostics of the Down syndrome without structural disorders of fetus - Zhanar Kurmangali; Kulyash Dzhamanaeva; Fred Ushakov; Mariya Useeva; Bakytkali Ibraimov (National Scientific Medical Center, 2017)
A case of prenatal diagnosis of Down's syndrome without combination with other pathologies of the fetus is described. The diagnosis was verified in a cytogenetic and pathoanatomical study. Conducting early diagnosis of this congenital fetal abnormality in the first trimester of pregnancy is topical and is of great importance in addressing the issue of the possibility of prolonging or aborting a pregnancy, postnatal examination and the necessary treatment of the revealed disorders.